New trends in sub-Riemannian geometry AMS-EMS-SMF Special Session Sub-Riemannian Geometry and Interactions July 18–22, 2022 Université de Grenoble-Alpes, Grenoble, France - Baudoin, Fabrice 1975-; Rizzi, L. 1984- (American Mathematical Society, 2025)
This volume contains the proceedings of the AMS-EMS-SMF Special Session on Sub-Riemannian Geometry and Interactions, held from July 18–20, 2022, at the Université de Grenoble-Alpes, Grenoble, France. Sub-Riemannian geometry is a generalization of Riemannian one, where a smooth metric is defined only on a preferred subset of tangent directions. Under the so-called Hörmander condition, all points are connected by finite-length curves, giving rise to a well-defined metric space. Sub-Riemannian geometry is nowadays a lively branch of mathematics, connected with probability, harmonic and complex analysis, subelliptic PDEs, geometric measure theory, optimal transport, calculus of variations, and potential analysis. The articles in this volume present some developments of a broad range of topics in sub-Riemannian geometry, including the theory of sub-elliptic operators, holonomy, spectral theory, and the geometry of the exponential map.
Keywords: Konferenzschrift